1990
DOI: 10.1193/1.1585555
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wall Resistance of Lightgage Steel Stud Wall Systems

Abstract: Experimental investigations were conducted to evaluate the lateral load-deflection characteristics of lightgage steel stud/gypsum wallboard panel combinations subjected to lateral cyclic loads. In all, six 8′ × 8′ specimens were tested. A reasonable one-to-one correspondence between the strap area increase and the increase in the contribution from the strap to the overall loadcarrying capacity of the panel at intermediate and high drift ratios was observed. The panel lateral stiffness for a given stabilized cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 0 publications
1
39
0
1
Order By: Relevance
“…This observation is not unique to this study since previous studies, including those by Adham et al [1990] and Fulop and Dubina [2002], have shown similar results. The unique aspect of the tension-only member is the large gap of almost zero strength and stiffness T.-W. Kim, J. Wilcoski, and D. A. Foutch that develops between previous points of large deformations.…”
Section: Hysteresis Modelsupporting
confidence: 75%
“…This observation is not unique to this study since previous studies, including those by Adham et al [1990] and Fulop and Dubina [2002], have shown similar results. The unique aspect of the tension-only member is the large gap of almost zero strength and stiffness T.-W. Kim, J. Wilcoski, and D. A. Foutch that develops between previous points of large deformations.…”
Section: Hysteresis Modelsupporting
confidence: 75%
“…Studies concerning the steel flat strap X bracing behaviour include wall specimens realized with strap braces on one or both wall sides, different strap dimensions and steel material properties [4,23,25,27,28]. The experimental results highlighted that the compressed diagonal straps do not collaborate to the wall lateral strength [23].…”
Section: Literature Reviewmentioning
confidence: 92%
“…The experimental results highlighted that the compressed diagonal straps do not collaborate to the wall lateral strength [23]. Therefore, the design of the strap is a key issue in the seismic behaviour of CFS strap-braced stud walls and, for this reason, these studies were devoted to optimize the flat strap X bracing contribution in the wall lateral response.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…이 중 Fig. 1에 나타낸 스 터드패널 모듈러시스템은 용접 및 강재물량을 절감하는데 가 장 효과적이다 [4], [5], [6], [7], [8], [9] . 또한, 냉강성형형강 부재는 가공성이 탁월하기 때문에 단면의 형상을 사용 목적에 따라 다양화하여 사용할 수 있는 장점이 있다 [10] .…”
Section: 서 론unclassified